2019
DOI: 10.33050/atm.v3i2.909
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization Of Financial Information System To Support The Creation From Budget Costs Using e-Budgeting

Abstract: In an era of modernization as this is now very much in the development of applications that make use of the computer program. One of them, namely the creation of the budget costs using e-budgeting application. What is the e-budgeting? E-Budgeting is a financial system that is stored online with the aim of transparency for each party. This system is applied as documentation for the preparation of the budget is usually in an area. Anyone can access data budget compiled by a local government so hopefully can prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Indicators of technological development in an Islamic perspective are based on: QS. Al-Anbiya 21:80, Al-Imran 3:190, Al-Nahl 16:78, Al-Baqarah 2:30, with different studies concluded that it affects performance in information data collection related to understanding the science of technological developments [15]. The link between religion and science and technology is stronger with the existence of different studies on all ability indicators, the innovations carried out have a significant correlation with technological developments in the view of Islam [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indicators of technological development in an Islamic perspective are based on: QS. Al-Anbiya 21:80, Al-Imran 3:190, Al-Nahl 16:78, Al-Baqarah 2:30, with different studies concluded that it affects performance in information data collection related to understanding the science of technological developments [15]. The link between religion and science and technology is stronger with the existence of different studies on all ability indicators, the innovations carried out have a significant correlation with technological developments in the view of Islam [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…3. It is more efficient in operating costs and marketing costs because banking institutions simply collaborate with financial technology service providers in offering banking products to the public [13][14]. 4.…”
Section: Swot Analysis Of Financial Technology Implementation On the ...mentioning
confidence: 99%
“…Financial history and political economy likewise cause us to notice the corporate strategies behind choices to embrace or reject mechanical advancement [11]. These accept record of the expenses just as advantages of mechanical change, including the dangers just as opportunities guaranteed by development.…”
Section: Very Real Transformationmentioning
confidence: 99%